2014
DOI: 10.1002/hbm.22627
|View full text |Cite
|
Sign up to set email alerts
|

Automated volumetry and regional thickness analysis of hippocampal subfields and medial temporal cortical structures in mild cognitive impairment

Abstract: We evaluate a fully automatic technique for labeling hippocampal subfields and cortical subregions in the medial temporal lobe (MTL) in in vivo 3 Tesla MRI. The method performs segmentation on a T2-weighted MRI scan with 0.4 × 0.4 × 2.0 mm3 resolution, partial brain coverage, and oblique orientation. Hippocampal subfields, entorhinal cortex, and perirhinal cortex are labeled using a pipeline that combines multi-atlas label fusion and learning-based error correction. In contrast to earlier work on automatic sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
647
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 523 publications
(697 citation statements)
references
References 87 publications
(184 reference statements)
31
647
5
Order By: Relevance
“…Validation: This method has been validated using k-fold cross-validation against manual segmentation in an in-vivo dataset of older healthy controls and aMCI patients (Yushkevich et al, 2015b).…”
Section: Automated Segmentation Of Hippocampal Subfields (Ashs)mentioning
confidence: 99%
See 2 more Smart Citations
“…Validation: This method has been validated using k-fold cross-validation against manual segmentation in an in-vivo dataset of older healthy controls and aMCI patients (Yushkevich et al, 2015b).…”
Section: Automated Segmentation Of Hippocampal Subfields (Ashs)mentioning
confidence: 99%
“…These techniques were applied to a variety of diseases in small single-site studies and usually found subfield volumetry to be superior to standard whole hippocampal volumetry for the detection of hippocampal damage in the early stages of the disease process, for differentiating between diseases or for the investigation of structure/function relationships (e.g., Wang et al, 2006;Ballmaier et al, 2008;Mueller et al, 2008;Schobel et al, 2009;Neylan et al, 2010;Bender et al, 2013;Kerchner et al, 2014;SchoeneBake et al, 2014;Chao et al, 2014;Hsu et al, 2015;De Flores et al, 2015;Pluta et al, 2012;Yushkevich et al, 2015b). The promise of hippocampal subfield volumetry techniques however led to two unexpected developments that could potentially limit the usefulness of this approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,98 Nevertheless, this presents a more complex problem for functional and diffusion MRI as compared with the structural imaging we discuss here. Finally, in addition to imaging improvements, image analysis techniques (such as automated hippocampal segmentation 101 ) need to be developed to capture relatively smaller subfields or pathways, 70 such as the endfolial pathway, in atrophied hippocampi of elderly, mildly cognitively impaired, and AD patients.…”
Section: -T Mri Limitations and Challengesmentioning
confidence: 99%
“…There have been many efforts to use computer analysis to expand the diagnostic and prognostic data from MRI studies (30,31); however, these require nonroutine imaging sequences and advanced postprocessing not generally available outside of research studies. Furthermore, although many are proven effective at the sites where they are developed, dissemination of these advanced analytical techniques between institutions has proven challenging (32)(33)(34)(35). Like CSF measurements, sensitivity and specificity of hippocampal volume calculations have shown limited ability to predict who will convert from MCI to AD and are often combined with other biomarkers (36)(37)(38)(39)(40).…”
Section: Current Status Of Tests For Admentioning
confidence: 99%